Podocyte Injury Through Interaction Between Tlr8 and Its Endogenous Ligand miR-21 in Obstructed and Its Collateral Kidney - Masum, Md. Abdul; Ichii, Osamu; Elewa, Yaser Hosny Ali; Kon, Yasuhiro (Frontiers in Immunology, 2021)
While chronic kidney disease is prevalent in adults, obstructive nephropathy (ON) has been reported in both young and old patients. In ON, tubulointerstitial lesions (TILs) have been widely investigated, but glomerular lesions (GLs) have been largely neglected. Here, we show a novel mechanism underlying GL development in ON in young and old mice. TILs develop earlier than GLs owing to infiltration of inflammatory cells in the tubulointerstitium, but GLs develop following the activation of Toll-like receptor 8 (Tlr8) even though the absence of inflammatory cells infiltrating the glomerulus. TLR8 and interleukin 1 beta (IL1β) proteins colocalize with reducing podocyte function markers (PFMs), indicating the activation of TLR8 signaling in injured podocytes. Furthermore, glomerular and serum levels of miR-21, an endogenous ligand for Tlr8, were higher in the ON mouse model than in the sham control. The glomerular expression of Tlr8 positively correlates with miR-21 and the downstream cytokines Il1b and Il6 and negatively correlated with PFMs (Nphs1 and Synpo). We also show the colocalization of TLR8 and IL1β proteins with reducing PFMs in both obstructed and collateral kidney of young and old mice. Furthermore, in vitro study results revealed higher expression of Tlr8 and its downstream cytokines in glomeruli from obstructed kidneys following treatment with miR-21 mimic than in the control. In conclusion, the overexpression of Tlr8 may serve as a plausible mechanism underlying GL development in ON through podocyte injury.